Legal Formulation Policy on the Privacy Protection of Children and Persons with Disabilities in Indonesia - Nabella Maharani Novanta; Bunga Desyana Pratami (Asian Journal of Law and Humanity, 2022)
Law of the Republic of Indonesia Number 27 of 2022 Concerning Personal Data Protection (UU PDP) contains provisions regarding the privacy data of children and persons with disabilities which are specifically regulated. The rules regarding the protection of personal data are important, especially related to the development of technology which is growing very fast. The existence of the PDP Law must be motivated by the purpose of law as a tool to integrate and coordinate various interests in society by regulating the protection and limitations of these various interests. This paper is included in the type of normative juridical research with a prescriptive method using logic and legal reasoning. Using a statutory, philosophical, and conceptual approach, this study will examine the existing privacy regulations for children and persons with disabilities with the principles of protection and ideal rules regarding the privacy of children and persons with disabilities in the future. The results of the study show that there are still weaknesses in the protection of children and disabilities data, all data on children and persons with disabilities tends to be at risk of being misused because there is still a legal vacuum regarding technical rules for protecting children and disabilities data. Unfortunately, the PDP Law does not regulate the 'special' process in question. Furthermore, there is no definite age standard regarding the classification of children in the PDP Law. The PDP Law which regulates the privacy of children and persons with disabilities is not in accordance with the theory of legal protection.